Pharmacoeconomic comparison of insulin glargine and insulin detemir in diabetes mellitus type 2 - I. N. Dyakov; S. K. Zyryanov (Izdatelstvo OKI, 2020)
Second generation insulin analogue - insulin glargine 300 UI/ml (GLA-300) - can provide an effective control of Diabetes Mellitus (DM) with minimal risk of hypoglycemic events and prevent of cardiovascular complications or events (CVS). Pharmacoeconomic comparison of most used insulins - GLA-300 and detemir (IDet) has been based on indirect treatment comparison in DM Type 2. Materials and methods. Indirect treatment comparison was created according to published data of a real world evidence data for the treatment of DM Type 2 with GLA-300 and IDet, and common comparator - GLA-100 - has been used. Patients (%) who reached HbA1c target were indicated as an efficacy criteria. Odds ratios (OR) were calculated for clinical efficacy and severe hypoglycemia's rate comparisons for GLA-300 and IDet. Direct (cost of annual treatment, hypoglycemia correction, CVS treatment), indirect medical costs as well as indirect costs (GDP loses) were calculated for GLA-300 and IDet strategies. Sensitivity analysis has been performed for confirmation of the base scenario results. Results. GLA-300 has advantages vs IDet by efficacy and less risks of severe hypoglycemia (OR 1.27 CI 95 % 1.02; 1.58 and OR 0.72 CI 95 % 0.56; 0.88 accordingly). Probability of good control of DM Type 2 (based on target of HbA1c<7.0 %) was higher on 27 % in GLA-300. Costs of insulins, expenditures for CVS treatment and payment for temporary disability were similar for GLA-300 and IDet groups (for the one-year treatment period), in the same time in GLA-300 group the less expenditures for hypoglycemia were observed. Total expenditures were slightly less for GLA-300 on 3.7 % vs IDet.Conclusion. GLA-300 and IDet have no economic advantages between groups in total costs, but GLA-300 has tended for economic benefi ts in compare with IDet in DM Type 2.